(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
It is possible and necessary to teach a foreign language not only as a new code, as a new way of expressing thoughts, but also as a source of information about the national culture of the native speaker of the target language. Thus, it is elucidated in the article that, when learning a foreign language, socio-cultural component as means of enhancing the efficiency of the educational process is of overriding importance